Symptomatic post‐thrombolytic intracerebral hemorrhage is not related to the cause of stroke. (3rd September 2016) - Curtze, S.; Sibolt, G.; Melkas, S.; Mustanoja, S.; Haapaniemi, E.; Putaala, J.; Sairanen, T.; Tiainen, M.; Tatlisumak, T.; Strbian, D.
Abstract : Background and purpose : The development of intracerebral hemorrhage following intravenous thrombolysis (IVT) can be influenced by various confounders related to the underlying vessel and tissue conditions. There are some data on association of cause of the stroke and the hemorrhage transformation. We tested the hypothesis that the cause of stroke is associated with the development of symptomatic intracerebral hemorrhage (sICH) following IVT. Methods : A consecutive cohort of 2485 IVT‐treated patients at the Helsinki University Central Hospital was classified according to the Trial of ORG 10172 in Acute Stroke Treatment (TOAST) criteria. An sICH was classified according to the European Cooperative Acute Stroke Study II criteria. The associations of sICH with nominal, ordinal and continuous variables were analyzed in a univariate binary regression model and adjusted in multivariate binary regression models. Results : In univariate analyses, cardioembolism [odds ratio (OR), 1.14; 95% confidence interval (CI), 0.79–1.64] and large‐artery atherosclerosis (OR, 1.30; 95% CI, 0.85–2.00) were not associated with sICH, and small‐vessel occlusion was associated with lower odds for sICH (OR, 0.18; 95% CI, 0.06–0.57). When adjusted for previously identified factors associated with sICH, none of the TOAST categories was associated with a higher or lower frequency of sICH. Conclusions : The development of sICH in IVT‐treated patients is not related to the cause of stroke. Abstract : Clickhere for the corresponding questions to this CME article.